Clinical Accuracy of Structured‑Light vs Active‑Illumination Multi‑View Stereo 3D Facial Scanners: A Comparative Study - Supakanjanakanti, Danaiya; Witeerungrot, Teepawat; Patanalertpiboon, Nattawat; Santavalimp, Kanokporn (Thai Journal of Orthodontics, 2025)
Background: Three-dimensional facial scanners are widely used in medical and dental fields for diagnostics, treatment planning, and postoperative evaluations. While scanner specifications provide nominal accuracy, actual clinical accuracy may vary due to facial complexity. Objective: This study aimed to evaluate and compare the clinical accuracy of two 3D facial scanners with different technologies: the structured light system (Artec® Space Spider, Artec 3D, Luxembourg) and the active illumination multi-view stereo system (Lumio® 3D, Lumio 3D Corporation, Thailand). Materials and methods: Fourteen participants underwent simultaneous 3D facial scanning using both scanners. An examiner measured distances and displacements between imaginary lines defined by anatomical landmarks, both directly on the participants’ faces and on their 3D models. Measurements were categorized into three groups and analyzed using one-way ANOVA and the Kruskal-Wallis test. Deviations in displacements and distances between each scanner’s data and the direct measurements were evaluated using paired t-tests and Wilcoxon signed-rank tests (P < 0.05). Results: No statistically significant differences were found among the three measurement groups overall. However, a significant difference in displacement deviation was observed between the two scanners in the orbital and nasal regions. Conclusion: Artec® space spider and Lumio® 3D scanners showed no significant difference in facial scanning accuracy compared to the direct measurement method. However, significant discrepancies were noted in the eye and nose region, likely due to anatomical complexity and movement. These areas may require special attention for improved scanning precision.